HUBUNGAN KOMUNIKASI TERAPEUTIK DENGAN KESADARAN DIET RENDAH GARAM PADA PASIEN HIPERTENSI DI POLI UMUM PUSKESMAS UMBULSARI - Marwah (Jurnal Kesehatan dr. Soebandi, 2017)
Hypertension which is The Silent Killer can be prevented one of them by changing diet, namely by reducing salt consumption. Information is an important factor in the awareness of hypertensive patients in implementing a low salt diet. Nurses are able to provide information to patients through communication. Good communication is usually called therapeutic communication. The purpose of this study was to determine the relationship of therapeutic communication with awareness of low-salt diets in hypertensive patients in the Public Health Center of Umbulsari Health Center. The study design used an observational method with a cross sectional approach. Samples taken purposively were hypertension patients totaling 76 people. This research was conducted by observing nurses' therapeutic communication and giving questionnaires to hypertensive patients who met the inclusion criteria. After a bivariate analysis with lambda correlation test p value of 0,000 and correlation value of 0.702 which shows that there is a relationship of therapeutic communication with low salt diet awareness in hypertensive patients at the General Poly Puskesmas Umbulsari and strong correlation. Effective therapeutic communication can increase awareness in patients, especially in this study related to low-salt diets of hypertensive patients